Relationship between transformational leadership, talent development and succession planning in national secondary schools, Seremban District, Negeri Sembilan, Malaysia - Armugam, Banu (2020)
The Education Ministry in Malaysia is responsible for educating, guiding and developing future school leaders and has emphasized the importance of succession planning in education system. Principals are facing numerous challenges especially on the practice of succession planning program including identifying future leaders, retaining and developing employees’ leadership skills and key positions not filled by talented leaders in schools. This research sort to determine the perceptions of subject heads on the extent to which transformational leadership practice, talent development and succession planning practices in national schools and whether a relationship does exist between the practices of transformational leadership and talent development on succession planning in national school organizations. This study utilized “Seven- Pointed Star Model” for succession planning and management program. The theoretical framework that guided this study is Bandura’s social cognitive theory and situational leadership theory. The objectives of the study: a) to determine the level of transformational leadership, talent development and succession planning practices in Seremban national secondary schools; b) to determine the relationship between transformational leadership, talent development on succession planning practices; and c) to determine the contribution of selected factors on succession planning. This study used quantitative approach with simple random sampling method. The researcher used survey questionnaires that was administered among subject heads in randomly selected schools. A total of 250 valid questionnaires were analysed using SPSS. The findings revealed that subject heads perceived their principals to have practiced moderately of succession planning and talent development while high level practice of transformational leadership. The Pearson Product-moment correlation analysis indicates a significantly positive and strong relationship between the succession planning towards the principal transformational leadership and talent development. However, the results illustrate that, the correlation between the talent development and succession planning is stronger than that of the transformational leadership. Using the multiple regression analysis, talent development has the highest beta coefficient of .733 compared to transformational leadership .116 which shows that talent development makes the strongest unique contribution in explaining the succession planning. This study contributes to the existing literature where talent development found to have significant relations in the context of succession planning practices. However, this contribution contextualized with school setting on succession planning is yet to be imparted. From the theoretical aspect, this study hopes to contribute to the theory of leadership. It is implied that the school principals should be able to provide a great leadership characteristic and always ensure their high leadership performance is significantly related to succession planning.